Digital Adaptation and Perceptions of Architecture and Interior Design Students on Online Lecture Methods - Tita Cardiah; Andiyan Andiyan; Husna Izzati; Eliyana Firmansyah (AL-ISHLAH: Jurnal Pendidikan, 2022)
The COVID-19 pandemic has transformed educational practices globally, compelling a shift from traditional in-person learning to online modalities. This shift significantly impacted Architecture and Interior Design studio courses, which traditionally rely on hands-on, collaborative studio environments. This qualitative descriptive study explored the challenges faced by students during the transition to online studio-based learning. Data were collected via questionnaires distributed to Architecture and Interior Design students to examine their experiences and adaptation processes. Findings revealed that students encountered both virtual/digital and physical/non-physical obstacles. Digital limitations included inadequate access to technological devices and varying levels of digital literacy among students and lecturers. Physical challenges involved the lack of appropriate equipment and working environments at home. Additionally, students faced non-physical barriers such as changes in time management, learning methodologies, behavioral adjustments, psychological stress, and unstable internet connectivity. The transition to online studio learning involved more than technological adaptation. Effective learning outcomes were influenced by the availability of physical tools and the ability to adjust to new learning rhythms and psychological demands. These findings highlight the need for comprehensive strategies that address not only digital readiness but also physical infrastructure and student well-being. Further research is recommended to explore in depth the behavioral and psychological dimensions of this transition.